2012
DOI: 10.12659/msm.883348
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a low cost wheelchair on the quality of life of the disabled in the developing world

Abstract: SummaryBackgroundPeople with disabilities in the developing world do not have equal and adequate access to education, employment, or medical care. Their physical or mental condition, compounded by a lack of financial and technological resources, imposes a burden on both the family and the State. A wheelchair is a form of assistive technology which eases that burden for many. This study examines the impact of a simple, donated chair on the health, quality of life, and function of a subject population.Material/M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
89
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(95 citation statements)
references
References 20 publications
2
89
0
1
Order By: Relevance
“…Appreciating the commitment of the government to the rights of people with disabilities in provision of services 2 , the primary objective of this preliminary study was todetermine the extent of satisfaction among users of locally manufactured wheelchairs, as part of the process of monitoring social accountability Overall, the wheelchair users' satisfaction was relatively high. As with other developing countries [9][10][11][12] , participants were satisfied with wheelchair related aspects such as effectiveness of use, safety, and participation in activities, though a small proportion expressed satisfaction with service related aspects. This suggests that the locally manufactured wheelchairs were perceived to be appropriate in meeting the needs of the users.…”
Section: Eggers Et Almentioning
confidence: 61%
See 2 more Smart Citations
“…Appreciating the commitment of the government to the rights of people with disabilities in provision of services 2 , the primary objective of this preliminary study was todetermine the extent of satisfaction among users of locally manufactured wheelchairs, as part of the process of monitoring social accountability Overall, the wheelchair users' satisfaction was relatively high. As with other developing countries [9][10][11][12] , participants were satisfied with wheelchair related aspects such as effectiveness of use, safety, and participation in activities, though a small proportion expressed satisfaction with service related aspects. This suggests that the locally manufactured wheelchairs were perceived to be appropriate in meeting the needs of the users.…”
Section: Eggers Et Almentioning
confidence: 61%
“…With the commitment of the government to the rights of people with disabilities in provision of services 2 , the concerns of unsatisfied users should be addressed. Follow up studies should focus on the quality of life of the users 12 , and also identify if a correlation exists between the types of disabilities and the level of satisfaction of the wheelchair users.…”
Section: Eggers Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…28 As these authors illustrate, mobility may be limited by more than neurologic deficits. Shore and Juillerat 44 have shown that by increasing mobility through donated wheelchairs, neurologically impaired patients in Vietnam, Chile and India had a significant decrease in PUs. Their proposed explanation is that wheelchair propulsion maneuvers induce pressure relief.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Their study also demonstrated that increased community mobility was associated with increased access to care, decreased pain, increased positive mood and improved daily feelings about life. 44 One could posit that these additional benefits may also directly or indirectly affect PU development. Taken together, in regions of the world where SCI is hidden from society and/or where inaccessibility and adaptive equipment limitations make activity difficult, individuals with SCI enjoy less mobility and therefore incur greater PU risk.…”
Section: Risk Factorsmentioning
confidence: 99%